Монголын “Дундат зуун” - Гонгоржав, Уснэмэх (Historia Mongolarum, 2023)
In this article th author attempts to use the term "Middle Age" for Mongolian history. He proposes to classify the chronology into three periods: Early Middle Age, High Middle Age, Late Middle Age.